2022
DOI: 10.1037/pst0000447
|View full text |Cite
|
Sign up to set email alerts
|

Building strong therapeutic relationships quickly: The effect of the perceived working alliance on veterans’ intensive PTSD treatment outcomes.

Abstract: This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In the 2-week program psychoeducation, mindfulness and yoga were omitted, but the number of therapy sessions remained the same. The study concluded that the 2-week program could be considered non-inferior to the 3-week program in both clinical outcomes and satisfaction (Held et al, 2023). The study does not report the prevalence of comorbidity disorders in this veteran sample.…”
Section: Discussionmentioning
confidence: 78%
“…In the 2-week program psychoeducation, mindfulness and yoga were omitted, but the number of therapy sessions remained the same. The study concluded that the 2-week program could be considered non-inferior to the 3-week program in both clinical outcomes and satisfaction (Held et al, 2023). The study does not report the prevalence of comorbidity disorders in this veteran sample.…”
Section: Discussionmentioning
confidence: 78%
“…Veterans in this sample spoke about the desire for ongoing emotional support and accountability from mental health providers. The therapeutic alliance serves an important role in the success of TFT, including retention (Keller et al, 2010; Sijercic et al, 2021) and outcomes (Held et al, 2022; Keefe et al, 2022; Saraiya et al, 2023) and may be an important construct to measure throughout TFT, such as via the Working Alliance Inventory (Horvath & Greenberg, 1989). Irrespective of posttreatment symptom severity, many spoke about wanting to have contact with their therapist as little or as often as needed to ensure gains solidified and to bolster confidence in the use of skills.…”
Section: Discussionmentioning
confidence: 99%